Direct Numerical Simulation of Turbulence with Scalar Transfer around Complex Geometries Using the Immersed Boundary Method and Fully Conservative Higher-Order Finite-Difference Schemes - Nagata, Kouji; Suzuki, Hiroki; Sakai, Yasuhiko; Hayase, Toshiyuki (IntechOpen, 2010)
None